TAX PLANNING DENGAN PEMILIHAN BENTUK BADAN USAHA PADA PERUSAHAAN PERSEORANGAN - Andriani, Sri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Tax Planning is one of the ways to minimize the tax burden within the company including in the selection of the proper form of business to run the company's business, namely with the mepertimbangkan of tariff revenue, a reduction in taxable income (PKP), the liability of income recognition, bookkeeping, tax collection obligations, and accountability of tax debt. Minimization of tax burden can be done in various ways, ranging from a still frame of the taxation to which break the rules of taxation.Tax planning that has made the company especially with elections to form a business entity. This type of research is qualitative, descriptive. The results of this research indicate that cigarette companies do business entity forms of election to save taxes by choosing the form of individual business entities. The magnitude of the rate of income tax that will be payable every year between Individual Taxpayers with the tax payers the Agency is different, i.e. Individual Taxpayers using Taxpayer tariff progersif while the Agency using the fixed fee. Individual companies have had some keuntunngan among other things a faster decision making does not take into account the interests of many parties.